Radioisotope Scanning of the Stomach - Czerniak, P., M.D.; Sinkower, A., M.D.; Boner, G., M.B., B.Ch. (Nuklearmedizin - NuclearMedicine, 1964)
A preliminary report is presented of gastroscanning. 23 patients were examined, 4 of these were controls, 4 had thyroid disease, 9 were suspected of having malignant and 6 benign gastric diseases. The scans in those suspected of having malignant disease were abnormal except in two, who were found at surgery to have a normal stomach. Moreover, one of the patients suspected of having a benign gastric disease was found to have an abnormal scan and an adenocarcinoma of the stomach was removed at operation.Un report préliminaire sur la gastro-scintigraphie est présenté. 23 malades ont été examinés dont 4 cas de contrôle, 4 cas souffrant d’une thyréopathie et 9 malades suspects de maladies gastriques malines ainsi que 6 de maladies bénines. Les scintigrammes chez les malades suspects d’une maladie maline étaient anormaux sauf deux où l’opération montrait un estomac normal.De plus, un scintigramme anormal se montrait chez un malade qui était suspect d’une maladie gastrique bénine. Lors de l’opération on enlevait un adénocarcinome.Es wird ein vorläufiger Bericht über die Szintigraphie des Magens vorgelegt. Es wurden 23 Patienten untersucht, von denen 4 Kontrollfälle waren, 4 an Schilddrüsenerkrankungen litten und 9 auf maligne sowie 6 auf benigne Magenerkrankungen verdächtig waren. Die Szintigramme bei jenen Patienten, bei denen ein Verdacht auf eine maligne Erkrankung vorlag, waren abnormal bis auf zwei, bei denen sich bei der Operation ein normaler Magen fand. Weiters ergab sich bei einem Patienten, der nur auf eine benigne Magenerkrankung verdächtig war, ein abnormales Szintigramm; bei der Operation wurde ein Adenokarzinom des Magens entfernt.